Generalized Spline Method for Integro-Differential Equations of Fractional Order - Hasan, Nabaa N.; Hussien, Doaa A. (Iraqi Journal of Science, 2018)
In This paper generalized spline method and Caputo differential operator is applied to solve linear fractional integro-differential equations of the second kind. Comparison of the applied method with exact solutions reveals that the method is tremendously effective.